A high rate of rodent-mediated predation on artificial nests in hedgerows of an agricultural landscape in southern Chile. Issue 2 (3rd April 2021) - Gantz, Alberto G.; Valdivia, Carlos E.
ABSTRACT: We evaluate, experimentally, the relative rate of artificial nest predation in hedgerows in southern Chile. Predation on artificial eggs was extremely high, with rodents being the main nest predators.